Toll like receptor induces Ig synthesis in Catla catla by activating MAPK and NF-κB signalling. (January 2019) - Patel, Bhakti; Banerjee, Rajanya; Basu, Madhubanti; Lenka, Saswati S.; Paichha, Mahismita; Samanta, Mrinal; Das, Surajit
Graphical abstract: Highlights: TLR induction differentially activates fish immunoglobulin (IgZ, IgM) expression. ERK and NF-κB play crucial role in TLR-mediated IgZ and IgM synthesis. ERK inhibition attenuates NF- κB-triggered cytokine and immunoglobulin synthesis. TLR-ERK-NF-κB axis regulates bacterial and PAMP stimulated IgZ and IgM expression. Abstract: The molecular crosstalk of proximal innate immune receptor signaling mediated by Toll-like receptors (TLRs) is crucial in generating an adaptive immune response. The extracellular-signal regulated kinases (ERK) participate in propagating intracellular signals initiated by stimulated TLRs to transcription factors eliciting cytokine release. Although ERK signaling has been extensively studied in mammalian counterparts, very little is known about its existence in carps and its role in augmentation of immunoglobulin (Ig) synthesis. Therefore, to gain insights into the efficacy of MAP kinase cascade in orchestrating fish antigen receptor generation, Catla catla fingerlings were induced with various TLR agonists or pathogen associated molecular patterns (PAMPs). Analysis of upstream signaling events revealed that PAMPs stimulated the tissues leading to a significant upregulation (P < 0.001, One-way ANOVA) of different TLRs (TLR2, TLR3, TLR4 and TLR5) followed by activation of MyD88 dependent and independent pathway. Activation of ERK and NF-κB mediated cytokine production consequently triggered the enhanced expression of IgZ and IgM as was evident by qRT-PCR analysis, flow cytometry, immunoblotting and ELISA. Pretreatment with ERK inhibitor (UO126) antagonized PAMPs mediated TLR stimulation, leading to sequential downregulation of MyD88/NF-κB/cytokines via interrupting ERK/NF-κB signaling axis. Together these results demonstrate that TLR stimulation triggers IgZ and IgM production via activation of ERK and NF-κB in C. catla indicating that NF-κB mediated cytokine production and ERK1/2 signaling is not only functional in fish, but may be crucial for generation of Ig repertoire in lower vertebrates.